Determinants of Satisfaction’s students using E-Learning Platform: The Technology Acceptance Model Approach - Karoui, Chedia (Journal of Ecohumanism, 2025)
The rapid rise of e-learning, especially in the wake of the COVID-19 pandemic, has made it a crucial tool for maintaining educational continuity. Its effectiveness relies on the interaction between actors, particularly the learner community, whose satisfaction is a key factor in engagement. This study explores the determinants of this satisfaction using the Technology Acceptance Model (TAM), which identifies perceived usefulness and perceived ease of use as major elements of platform acceptance. Through a comprehensive literature review and an empirical survey conducted at a Tunisian university, the findings indicate that perceived ease of use has a stronger influence on learner satisfaction than perceived usefulness. These results provide valuable insights for enhancing e-learning systems and fostering their adoption in diverse educational and professional environments. The study contributes to the growing body of research on e-learning by offering actionable recommendations for improving the design and implementation of e-learning initiatives. These findings offer insights for improving e-learning systems in Tunisian universities and promoting their adoption in various educational and professional contexts.